Zbieżność cykli koniunkturalnych krajów członkowskich Unii Europejskiej a funkcjonowanie unii walutowej - Biegun, Krzysztof (Business Cycle Synchronization of the European Union States and the Effectivenss of Monetary Union, 2008)
In the context of a single currency the resemblance of the business cycles of the participating countries is a major concern. Some synchronization of shocks and cycles is required to have a single stance of monetary policy that is acceptable for individual countries. For instance, a common monetary policy expansion in response to a negative aggregate demand shock that is symmetric across countries should be adequate. In contrast, differences in cyclical situations and underlying shocks can complicate monetary policy. When cyclical situations are different, a single stance of monetary policy is then sub-optimal for the individual countries. Therefore, an important part of the costs to join the euro area or other currency areas depends on the synchronization of the business cycles. The aim of the first part of this article is to present the results of different analysis of business cycles correlation between euro area and member countries. The second part contains empirical results of analysis of the GDP growth correlation between some chosen European countries and the euro area. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 69-79